THE USING OF GIVING EXERCISE METHODE THROUGH NATURAL-BASED COLLAGE STUDENTS INCREASING CREATIVITY AND MOTORIC SKILL - Ira Permatasari; Johanes Sapri; Nina Kurniah (DIADIK, 2017)
This research conducted to investigate the effect of giving the exercise through natural-based collage methode toward increasing fine motoric skill on B1 class PAUD Semarak Sanggar. This Research, was classroom action research, where the subject was 17 students in B1 class of Paud Semarak Sanggar Arga Makmur. Furthermore, the researcher observed the teacher and the students.Then, the researcher used the means score to see the effect oh this methode. In adition, the result of this research showed that there was a significant effect of increasing the creativity and the fine motoric skill through giving exercise methode. The result of increasing creativity in which, t-obtain > t-table (2,281 > 1,746). Furthermore, increasing of fine motoric skill showed that t-obtain > t-table (3,665 > 1,746) it means that Ho rejected. It can be concluded that, giving exercise methode through natural-based collage was has a significant effect of increasing the creativity and fine motoric skill students. Keywords: giving exercise methode, natural-based collage, creativity, fine motoric skill